How Can Educators Effectively Be Trained to Teach Coding and Robotics in STEAM Field Programmes? - De Jager, Thelma (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2023)
Robotics is predicted to become the fastest growing market that could contribute to global socio-economic prosperity. The increasing unemployment rate and demand for 21st-century skills dictate the development of coding and robotic skills in STEAM fields. Schools are implementing the development of coding and robotics skills in curricula, but teachers are not effectively trained for teaching these skills. Therefore, the study employed a qualitative approach to detect how educators (n=22) of a higher education institution could be effectively trained in coding and robotics. The results showed that educators preferred working collaboratively in small groups, enjoyed the training activities, observed and understood the application of theory into practice, still required hard copy manuals, found robotic kit components too small to work on, were dependent on individual support during the training sessions, and required additional training sessions. Best practice in training coding and robotics is to ensure technical and pedagogical knowledge is connected and applied to real-life practices; divide trainees into basic and beginner classes, and sub-divide them in pairs where they can work collaboratively and interactively in completing their coding and robots; clarify the advantages and disadvantages of robotics in society; create fun activities during the training; and ensure sufficient support is available after training to assist those still not at ease with coding a robot.